The influence of coffee candy product placement in Korean dramas on brand image and brand awareness among netflix users - Dwi Rani Rahayu; Khairina Tambunan; Nurbaiti Nurbaiti (LPMP Imperium, 2026)
Coffee candy’s product placement in Korean dramas is used as a strategy to strengthen brand image and increase brand awareness among Netflix users. Coffee candy, as a local Indonesian brand, leverages the popularity of Korean dramas to reach the global market through strategic product placement. A quantitative approach was used, with a survey of 101 Netflix user respondents in Medan who had watched Korean dramas featuring coffee candy. The sampling technique was purposive, and the data were analyzed using simple linear regression. The results showed that Coffee candy’s product placement had a significant effect on brand image (R2 = 0,774) and brand awareness (R2 = 0,858). Public interest statements These findings confirm that product integration in entertainment content can effectively strengthen brand perception and understanding, as well as encourage purchasing interest among young consumers. This strategy has proven relevant in modern marketing communications, especially in the digital era, which is characterized by cross-border content.